The Economics of Migrants? Remittances - Hillel Rapoport; Frédéric Docquier (Institute for the Study of Labor (IZA), 2005)
This chapter reviews the recent theoretical and empirical economic literature on migrants' remittances. It is divided between a microeconomic section on the determinants of remittances and a macroeconomic section on their growth effects. At the micro level we first present in a fully harmonized framework the various motivations to remit described so far in the literature. We show that models based on different motives share many common predictions, making it difficult to implement truly discriminative tests in the absence of sufficiently detailed data on migrants and receiving households' characteristics and on the timing of remittances. The results from selected empirical studies show that a mixture of individualistic and familial motives explains the likelihood and size of remittances. At the macro level we first briefly review the standard (Keynesian) and the trade-theoretic literature on the short-run impact of remittances. We then use an endogenous growth framework to describe the growth potential of remittances and present the evidence for different growth channels. We then explore the relationship between remittances and inequality. This relationship appears to be non-monotonic. This is consistent with different theoretical arguments regarding the role of migration networks and/or the dynamics of wealth transmission between successive generations.
Keywords: O15; D31; J61; 330; remittances; migration; income distribution; private transfer